Modelo de selección de un esquema óptimo de cooperación entre estaciones móviles (2017)
"Mobile telecommunication is one of the most dynamic and competitive sectors in the world. In the last years, this sector has shown a continuous growth in the infrastructure installed by the operators, as well as in the number of subscriptions, and new services and/or applications deployed. This environment generates a significant increasing in the data traffic over the networks. The main drawbacks generated by this continuous growth are related with capacity, coverage and interference in the access network, especially in densely populated urban areas... This dissertation seeks to contribute to network management strategies through the development of decision-making algorithms specific to define the possibilities to use cooperation techniques between base stations. Through these algorithms it is intended that the operator can not only optimize the resources utilization of the deployed infrastructure, at the same time that it generates an improvement in the users' perception of quality of the services." -- Tomado del Formato de Documento de Grado.